2017
DOI: 10.1161/circulationaha.116.024921
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Obesity and the Risk of Atrial Fibrillation

Abstract: Background Observational studies have identified an association between body mass index (BMI) and incident atrial fibrillation (AF). Inferring causality from observational studies, however, is subject to residual confounding, reverse causation, and bias. The primary objective of this study was to evaluate the causal association between BMI and AF using genetic predictors of BMI. Methods We identified 51 646 individuals of European ancestry without AF at baseline from seven prospective population-based cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 99 publications
(26 citation statements)
references
References 72 publications
4
20
0
Order By: Relevance
“…This approach can be a strong alternative for better understanding the sex-specific nature of the associations of risk factors with AF. A recent large-scale Mendelian randomization study has confirmed a causal relationship between BMI and incident AF (63). However, sex differences were not reported.…”
Section: Discussionmentioning
confidence: 98%
“…This approach can be a strong alternative for better understanding the sex-specific nature of the associations of risk factors with AF. A recent large-scale Mendelian randomization study has confirmed a causal relationship between BMI and incident AF (63). However, sex differences were not reported.…”
Section: Discussionmentioning
confidence: 98%
“…One possibility is that the associated comorbidities of type 2 diabetes, namely hypertension and obesity, are the causal link between type 2 diabetes and atrial fibrillation. In fact, a recent Mendelian randomisation analysis showed a causal relationship between BMI and incident atrial fibrillation [11].…”
Section: Discussionmentioning
confidence: 99%
“…In a Mendelian randomization analysis of genetic alleles associated with obesity, Chatterjee et al 10 explored the relationship between obesity and AF in 51 646 patients of European decent. They found strong support for a causal link between obesity and AF and a basis for public health interventions.…”
Section: Genetics Of Afmentioning
confidence: 99%